Yemeni Consumers’ Perception and Attitude towards Asian made Products - Yassin, Ammar; Baharun, Rohaizat (Indian Journal of Marketing, 2010)
Due to globalization of trade, a stream of research has emerged from the notion of country-of-origin (COO). It is the information which can influence consumers’ product perceptions (Nebezahl et al., 2003). COO is the most researched international aspect of consumer behaviour (Tan and Farley, 1987; Heslop et al., 1998). Despite the plethora of studies conducted on the subject, there has been a lack of knowledge on the perceptions of Arab consumers on foreign products. One of the most widely studied areas of international marketing has been the impact of COO on the consumer’s perception of products from both developing and developed nations (Samiee, 1994; Peterson and Jolibert, 1995). More than 400 academic (peer-reviewed) articles have been published over 40 years, with a great deal of diversity of consumers surveyed (Usunier, 2006). COO research has concentrated on the examination of consumer product perceptions and/or attitudes towards products made in different countries based on a variety of intrinsic or extrinsic cues.